2021
DOI: 10.1017/s0007114521001355
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of whey protein concentrate admixtured of curcumin on metabolic control, inflammation and oxidative stress in Wistar rats submitted to exhaustive exercise

Abstract: This work aimed to evaluate the effects of whey protein concentrate admixtured of curcumin on metabolic control, inflammation and oxidative stress in Wistar rats submitted to exhaustive exercise. A total of 48 male rats were divided into 6 experimental groups (n = 8): standard diet group (AIN-93M); standard diet submitted to exhaustion test group (AIN-93M ET); whey protein concentrate admixtured of curcumin group (WPC + CCM); WPC + CCM submitted to exhaustion test group (WPC + CCM ET); CCM group, and CCM subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…To address these issues, the inclusion of antioxidants such as curcumin in the diet has been considered. Conceição et al suggested that a combination of whey protein concentrate and curcumin could potentially decrease the expression of inflammatory cytokines and increase that of anti-inflammatory cytokines [ 47 ]. Furthermore, a mixture of cinnamon and turmeric has been shown to maintain and enhance antioxidant enzyme activities.…”
Section: Curcumin In Stress Management Of Terrestrial Animalsmentioning
confidence: 99%
“…To address these issues, the inclusion of antioxidants such as curcumin in the diet has been considered. Conceição et al suggested that a combination of whey protein concentrate and curcumin could potentially decrease the expression of inflammatory cytokines and increase that of anti-inflammatory cytokines [ 47 ]. Furthermore, a mixture of cinnamon and turmeric has been shown to maintain and enhance antioxidant enzyme activities.…”
Section: Curcumin In Stress Management Of Terrestrial Animalsmentioning
confidence: 99%
“…Protein from whey is arguably the most researched type of protein in relation to curcumin, in the form of whey protein isolate (WPI) [ 154 , 155 , 156 , 157 , 158 ], as well as whey protein concentrate (WPC) [ 158 , 159 , 160 , 161 , 162 , 163 , 164 ]. However, while both WPI and WPC come from whey, there is a significant difference between them in terms of processing and final product composition.…”
Section: Curcumin Bioavailability Improvingmentioning
confidence: 99%